The American Psychiatric Publishing textbook of psychiatry - Hales, Robert E.; Yudofsky, Stuart C.; Roberts, Laura Weiss, 1960- (American Psychiatric Publishing, 2014)
The only comprehensive psychiatry textbook to integrate all the new DSM-5 criteria, this acclaimed gold standard has been revised, updated, and restructured to serve as a practical, authoritative guide for a new era in psychiatric education and practice. This volume is the definitive reference for students, residents, and clinicians.